Purchase Gap between Intention and Behaviour for Green Products among Consumers - Vidhyakala,, K.; Santhi, P. (International Journal of Psychosocial Rehabilitation, 2024)
Promotion of green technology and green products is necessary for conservation of natural resources and sustainable development. Today, understanding is increasingly focusing on how to help people whose environments are not optimal to avoid hazards. The consumers who understand the benefits of green products have the opportunity to reduce their personal influences to promote eco friendly environment which is good for their health and contributes for long life. Hence, the actual purchase behaviour of green products was significantly affected by the purchase intention of the products. In order to indentify factors influencing purchase gap between the green products purchase intention of the consumers and purchase behaviour, the Theory of Planned Behaviour used to identify effect of consumers’. The result from the analysis indicates that the respondents’ intentions to buy green products were influenced by environmental concern, attitude on environmental issues, attitude towards green products and collectivism.